2011
DOI: 10.1029/2011eo470002
|View full text |Cite
|
Sign up to set email alerts
|

Does gender bias influence awards given by societies?

Abstract: AGU is a participant in a U.S. National Science Foundation (NSF)–funded project called Advancing Ways of Awarding Recognition in Disciplinary Societies (AWARDS), which seeks to examine whether gender bias affects selection of recipients of society awards. AGU is interested in learning why there is a higher proportion of female recipients of service and education awards over the past 2 decades. Combined with a lower rate of receipt of research awards, these results suggest that implicit (subconscious) bias in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 4 publications
(2 reference statements)
1
27
0
Order By: Relevance
“…Past Eos writers and others have done a thorough job of quantifying the gender disparity in award granting and have suggested a number of reasons that might account for it. Holmes et al [2011] detail a past review of gender distribution in AGU awards in association with the Advancing Ways of Awarding Recognition in Disciplinary Societies ( AWARDS) project, which is funded by the U.S. National Science Foundation. The article found that women were more likely to be nominated for service and education awards than research awards and suggested that implicit biases might lead nominators to think of women in a personal light rather than a professional one.…”
Section: Forummentioning
confidence: 99%
“…Past Eos writers and others have done a thorough job of quantifying the gender disparity in award granting and have suggested a number of reasons that might account for it. Holmes et al [2011] detail a past review of gender distribution in AGU awards in association with the Advancing Ways of Awarding Recognition in Disciplinary Societies ( AWARDS) project, which is funded by the U.S. National Science Foundation. The article found that women were more likely to be nominated for service and education awards than research awards and suggested that implicit biases might lead nominators to think of women in a personal light rather than a professional one.…”
Section: Forummentioning
confidence: 99%
“…But, again, as with the response to Druffel [ 1994 ], which possibly increased the number of female Fellows, the increased number of female medalists may have been in response to Holmes et al . [ 2011 ].…”
Section: Page 99mentioning
confidence: 99%
“…A continued look at this data supports the hypothesis that women are overlooked for honors, especially election as With such small numbers, it is impossible to identify a specific cause. But, again, as with the response to Druffel [1994], which possibly increased the number of female Fellows, the increased number of female medalists may have been in response to Holmes et al [2011]. Their brief report described the results of an Association for Women in Science (AWIS) analysis, which depicted underrepresentation of women among awardees of four scientific societies that cannot be explained by the percentage of women in the field.…”
Section: Nasa/bill Ingallsmentioning
confidence: 99%
“…Practices to reduce these biases in award nominations and selections have been developed by AWIS. This information, presented in Eos by Holmes et al [2011], may have alerted AGU members, especially those on awards committees, to identify remarkable female scientists. Both of the female medalists who became new Fellows were more than 26 years post -Ph.D., suggesting that they may have been overlooked for earlier nomination to become a Fellow despite their achievements.…”
Section: Nasa/bill Ingallsmentioning
confidence: 99%